Impact of virtual influencers on customer engagement of Generation Z consumers: a presence perspective - Lin, Qiaoling; Ng, Siew Imm; Kamal Basha, Norazlyn; Luo, Xi; Li, Yingxia (Emerald Publishing, 2024)
Purpose: Based on the computers as social actors (CASA) theory, this study aims to explore the impact of three characteristics of virtual influencers (conversational tone, autonomy and responsiveness) on social presence, telepresence and customer engagement. Design/methodology/approach: Using the purposive sampling technique, online survey was administered to Chinese Gen-Z consumers engaging with virtual influencers. Subsequently, 357 respondents were sampled. SPSS 29.0 and Smart PLS 4.0 were used to perform the analyses. Findings: The results show that conversational tone and responsiveness have significant positive effects on both social presence and telepresence. Autonomy has a positive effect on telepresence, but not social presence. Social presence and telepresence have a positive impact on customer engagement. Originality/value: As a burgeoning field, there is still uncertainty among both practitioners and researchers about the methods that virtual influencers engage their users in the context of social media. Limited research has focused on presence (social presence and telepresence) due to virtual influencers. Therefore, the CASA theory offers valuable insights into how virtual influencers’ characteristics contribute to the presence and customer engagement and provides practical guidance for the design of virtual influencers.